Pengaruh Lokasi, Persepsi Harga dan Kualitas Pelayanan terhadap Keputusan Menginap dan untuk Meningkatkan Loyalitas Pelanggan di Gran Melia Jakarta - Muhammad Farhan; Surono Surono (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
The aim of this research was to examine how factors such as location, perceived price, and service quality impact the choice to stay and enhance customer loyalty at Gran Melia Jakarta. To conduct this study, a questionnaire was utilized as a research tool, and a total of 150 respondents were analyzed as samples. The research employed the Primary Quantitative Research Methods: Cross-sectional surveys. Accidental sampling was employed as the sampling technique. The analysis method employed was Partial Least Squere (PLS). The findings of this study indicate that location does not have an influence on the decision to stay. However, price perception and service quality significantly affect the decision to stay, and the decision to stay has a significant impact on customer loyalty. The outcomes of this study are anticipated to serve as valuable insights for decision-making by the management of Hotel Gran Melia Jakarta to enhance purchasing decisions.